Immunological Responses, Expression of Immune-Related Genes, and Disease Resistance of Rainbow Trout (Oncorhynchus mykiss) Fed Diets Supplied with Capsicum (Capsicum annuum) Oleoresin - Sevdan Yilmaz; Osman Nezih Kenanoğlu; Sebahattin Ergün; Ekrem Şanver Çelik; Mert Gürkan; Elsayed Eldeeb Mehana; Hany M. R. Abdel-Latif (Animals)
A 45-day feeding study was carried out to assess the immune-stimulatory effects of capsicum oleoresin when added to rainbow trout diets. A total of 450 fish (mean weight: 155.20 ± 1.96 g) were distributed into 400 L tanks (30 fish/tank) across five experimental groups: control (CT, 0%), C7 (0.7%), C14 (1.4%), C21 (2.1%), and C28 (2.8%). Each group consisted of three replicate tanks. At the end of this period, hemato-biochemical parameters, innate immune responses, and immune-related gene expression levels were evaluated, and a histological examination of head kidney and liver sections was conducted. Finally, fish in all groups were challenged with Lactococcus garvieae and observed for an additional 20 days. The results revealed that oleoresin supplementation enhanced the immune responses of the treated fish, which was evidenced by the increased globulin, total protein, respiratory burst activity, and total immunoglobulin levels. The highest expression levels of the il-8, il-1β, TGF-β, and SAA genes was noticed in the C7 group, as compared with the results for the other groups. The IgT gene expression levels were higher in all experimental groups than in the CT group, and this increase was at the highest level in the C28 group. Following the bacterial challenge, all experimental groups displayed higher survival rates compared to that of the CT group. These values were 75.93, 72.22, 46.30, 33.33, and 29.63% in the C7, C14, C21, C28, and CT groups, respectively, with the C7 group displaying the highest survival rate among the groups. The histological examination of liver and head kidney tissues revealed that higher doses (in the C21 and C28 groups) showed an increase in cytoplasmic vacuolization, which causes adverse effects on fish health. However, the C7 group displayed normal histological structure in both tissues. Taken together, the most favorable immune responses were achieved in the C7 group, suggesting that 0.7% oleoresin could be applied to rainbow trout to boost immunity and protect the fish from diseases.